Colonic malignant peripheral nerve sheath tumour in a cat. Issue 1 (May 2019) - Boland, Lara; Setyo, Laura; Sangster, Cheryl; Brunel, Laurencie; Foo, Timothy; Bennett, Peter
Case summary: A 14-year-old male neutered domestic mediumhair cat presented with a 4 month history of inappetence and weight loss. Pertinent abnormalities on haematology and biochemistry included a mild microcytic regenerative anaemia (packed cell volume [PCV] 24% [reference interval (RI) 30–45%], mean cell volume 30.8 fl [RI 40–45 fl], absolute reticulocyte count 326.8 × 10 12 ) and increased alkaline phosphatase activity (76 IU/l; RI <50 IU/l). Abdominal ultrasound and CT scan revealed masses in the transverse colon (2.0 cm × 1.2 cm) and right medial liver lobe (5.0 cm diameter). Thoracic radiographs were unremarkable. Right medial liver lobe resection and colectomy were performed. Immunohistochemistry was positive for S-100 protein, vimentin and glial fibrillary acidic protein, very weakly positive for c-kit and negative for muscle-specific actin and CD18, consistent with a colonic malignant peripheral nerve sheath tumour (MPNST) with a hepatic metastasis. Postoperative treatment with metronomic cyclophosphamide was well tolerated. Eighteen months postoperatively the cat re-presented after 3 days of progressive lethargy and inappetence. Haematology revealed a marked non- or pre-regenerative anaemia (PCV 10%). Coagulation times were prolonged (prothrombin time 39 s [RI 15–22 s] and activated partial thromboplastin time >300 s [RI 65–119 s]). Abdominal ultrasound identified multiple renal and hepatic nodules. Euthanasia was performed and post-mortem examination confirmed metastasis of the MPNST. Relevance and novel information: This report describes the treatment of a metastatic colonic peripheral nerve sheath tumour in a cat. Feline visceral MPNSTs are rare and little is known about prognosis or optimal treatment.